Association between teenage mothers and acute infections in children under five in Peru from 2015-2019 - Jerry K. Benites-Meza; Percy Herrera-Añazco; Nilton Yhuri Carreazo; Guido Bendezu-Quispe; Anderson N. Soriano-Moreno; Vicente A. Benites-Zapata (Instituto Materno Infantil de Pernambuco, 2024)
Abstract Objectives: to assess the association between mothers age and the presence of acute respiratory infections (ARIs) and acute diarrhea (AD) in Peruvian children under five years old. Methods: secondary analysis of the database of the "Demographic and Family Health Survey" of 2015 and 2019. We analyzed data from children under five and their reproductive-age mothers who live in the same household. Poisson regression models were used to generate adjusted prevalence ratios (aPR) with 95% confidence intervals (95%CI) to assess the association between mothers' age group and the presence of ARIs and AD in their children. Results: 84,671 mother/child data were analyzed. In the adjusted regression model, being a young mother (aPR= 1.18; 95%CI= 1.11-1.25; p<0.001) or an teenage (aPR= 1.11; 95%CI= 1.01-1.22; p=0.045) were associated with a higher prevalence of ARIs in their children. In addition, being a young mother a teenage (aPR= 1.18; 95%CI= 1.11-1.25; p<0.001) or a teenage (aPR= 1.22; 95%CI= 1.10-1.35; p<0.001) were also associated with a higher prevalence of AD cases in their children. Conclusions: mothers' age was found to be associated with the prevalence of ARIs and AD in Peruvian children under five, with teenagers and young mothers having the greatest probability of ARIs and AD.